ChemInform Abstract: A New High Pressure Form of Ba3NiSb2O9. Issue 24 (27th May 2016) - Darie, Celine; Lepoittevin, Christophe; Klein, Holger; Kodjikian, Stephanie; Bordet, Pierre; Colin, Claire V.; Lebedev, Oleg I.; Deudon, Catherine; Payen, Christophe
Abstract: Polycrystalline samples of 6H‐B Ba3 NiSb2 O9 are obtained from the ambient pressure 6H‐A modification by hot‐press sintering (anvil cell, 2—4 GPa, 400—680 °C).